PAJAK PENGHASILAN DAN KEPUTUSAN PENDANAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA) - Purnamasari, Yenny (Widya Mandala Surabaya Catholic University, 2009)
This research has a purpose to provide empirical testing about influencing of income tax which is used as management consideration to make financial decisions. The examined factors on this research are tax and non tax factors. leverage policy, and dividend policy. The sample consist of 32 manufacturing companies, which are listing in Indonesian Capital Market. is chosen bv purposive sampling.' Moreover, the statistic method lIsed to test on the research hypothesis is Multivariate Multiple Regressions. The results show that income tax is one of the consideration management factors for making goodfinancial decisions. The results also proved that leverage and dividend policy are significantly influenced by income tax.